2016
DOI: 10.1002/2016jb013228
|View full text |Cite
|
Sign up to set email alerts
|

A 2‐D tomographic model of the Juan de Fuca plate from accretion at axial seamount to subduction at the Cascadia margin from an active source ocean bottom seismometer survey

Abstract: We report results from a wide‐angle controlled source seismic experiment across the Juan de Fuca plate designed to investigate the evolution of the plate from accretion at the Juan de Fuca ridge to subduction at the Cascadia margin. A two‐dimensional velocity model of the crust and upper mantle is derived from a joint reflection‐refraction traveltime inversion. To interpret our tomography results, we first generate a plausible baseline velocity model, assuming a plate cooling model and realistic oceanic lithol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
103
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(119 citation statements)
references
References 87 publications
12
103
0
2
Order By: Relevance
“…In the outer rise region of the incoming plates, our data reveal an abrupt transition across 46°N from extremely low seismicity in the north to high seismicity in the south. In contrast, offshore Oregon, large offset normal faults that transect the oceanic crust and extend~6-7 km into the uppermost mantle were imaged, accompanied by a reduction in V p in the lower crust Horning et al, 2016). This inference is consistent with structural observations from active source seismic studies (Canales et al, 2017;Gulick et al, 2001;Han et al, 2016Han et al, , 2017Horning et al, 2016).…”
Section: Discussionsupporting
confidence: 75%
“…In the outer rise region of the incoming plates, our data reveal an abrupt transition across 46°N from extremely low seismicity in the north to high seismicity in the south. In contrast, offshore Oregon, large offset normal faults that transect the oceanic crust and extend~6-7 km into the uppermost mantle were imaged, accompanied by a reduction in V p in the lower crust Horning et al, 2016). This inference is consistent with structural observations from active source seismic studies (Canales et al, 2017;Gulick et al, 2001;Han et al, 2016Han et al, , 2017Horning et al, 2016).…”
Section: Discussionsupporting
confidence: 75%
“…Several large V‐shaped propagator wakes disrupt the seafloor age progression (Figure b) as well as the structure of the lithosphere. Active source studies have identified anomalously slow crustal and uppermost mantle velocities beneath seafloor created at migrating ridge offsets interpreted as regions of increased plate hydration (Han et al, ; Horning et al, ; McClymont & Clowes, ; Soule et al, ; Weekly et al, ). In reflection studies, propagator wakes often appear as regions of anomalous crustal and mantle reflectivity (Han et al, , ; Nedimović et al, ).…”
Section: Geologic Settingmentioning
confidence: 99%
“…Prior to subduction, the plate is <10 Myr old, which has led to the inference of a largely dry lithosphere particularly at sub‐Moho depths where elevated temperatures limit the depth extent of brittle deformation. Indeed, recent estimates of Juan de Fuca (JdF) mantle hydration from 2‐D active‐source imaging indicate less than 0.25 wt% H 2 O within the uppermost 1 km of mantle (Canales et al, ; Horning et al, ). A relatively dry subducting slab is also consistent with a general lack of deep intraslab seismicity (McCrory et al, ) and eruption of dry arc magmas (Ruscitto et al, ; Walowski et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations